A remarkable case of gout in the Imperial Rome: Surgery and diseases in antiquity by osteoarchaeological, paleopathological, and historical perspectives. (23rd July 2019) - Fornaciari, Gino; Marinozzi, Silvia; Messineo, Daniela; Caldarini, Carla; Zavaroni, Federica; Iorio, Silvia; Sveva, Longo; Capuani, Silvia; Catalano, Paola; Gazzaniga, Valentina
Abstract: This study is the result of a multidisciplinary approach and focuses on a case of considerable historical and medical interest. The work originally stemmed from findings at a funerary site in the area of Casal Bertone in Rome (Italy), regards an individual in a tomb identified simply by the number "75." The skeletal alterations that were later discovered gave rise a debate among the members of the team. Challenges in identifying the pathology have brought historians, anthropologists, and radiologists into the field with the use of sophisticated equipment, including CT scans and X‐ray equipment, as well as some analyses carried out with the latest spectrometers. Consequently, the most likely diagnostic hypothesis resulted in gout. During this work, each area of study dealt with the problem in a different manner, allowing for a greater understanding of gout at this point in history, how this pathology might have influenced a person's life, as well as the medical approaches and techniques used to treat it in the imperial age of the second century BCE.